2004
DOI: 10.1101/gad.1173204
|View full text |Cite
|
Sign up to set email alerts
|

The NAD+-dependent Sir2p histone deacetylase is a negative regulator of chromosomal DNA replication

Abstract: The establishment of DNA synthesis during the S phase is a multistep process that occurs in several stages beginning in late mitosis. The first step is the formation of a large prereplicative complex (pre-RC) at individual replication origins and occurs during exit from mitosis and entry into G1 phase. To better understand the genetic requirements for pre-RC formation, we selected chromosomal suppressors of a temperature-sensitive cdc6-4 mutant defective for pre-RC assembly. Loss-of-function mutations in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
106
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(114 citation statements)
references
References 89 publications
7
106
1
Order By: Relevance
“…Alternatively, the hyopacetylation of H4K16 in these regions could be due to transient Sir2 association not captured by ChIP-Seq. Previous studies have shown that Sir2, but not Sir3 or Sir4, controls some origins of replication (Pappas et al 2004;Crampton et al 2008;Yoshida et al 2014). However, MACS did not detect any significant enrichment for Sir2 at subtelomeric ARSs outside the core X element.…”
Section: Catalytic Activity Of Sir2 At Telomeresmentioning
confidence: 56%
“…Alternatively, the hyopacetylation of H4K16 in these regions could be due to transient Sir2 association not captured by ChIP-Seq. Previous studies have shown that Sir2, but not Sir3 or Sir4, controls some origins of replication (Pappas et al 2004;Crampton et al 2008;Yoshida et al 2014). However, MACS did not detect any significant enrichment for Sir2 at subtelomeric ARSs outside the core X element.…”
Section: Catalytic Activity Of Sir2 At Telomeresmentioning
confidence: 56%
“…Temperature-sensitive mutations in the pre-replication complex components ORC, CDC6, and MCM can be suppressed by inactivation of SIR2, a histone deacetylase (HDAC; Pappas et al 2004). The HDAC Sir2p is also a negative regulator of chromosomal DNA replication (Pappas et al 2004) and controls the frequency of DNA replication origin firing within rDNA (Pasero et al 2002).…”
Section: Chromatin Modifications At Dna Replication Originsmentioning
confidence: 99%
“…The HDAC Sir2p is also a negative regulator of chromosomal DNA replication (Pappas et al 2004) and controls the frequency of DNA replication origin firing within rDNA (Pasero et al 2002). Some yeast ARS elements contain specific sequences recognized by Sir2p that inhibit DNA replication origin activity, most likely by affecting the local chromatin structure (Crampton et al 2008).…”
Section: Chromatin Modifications At Dna Replication Originsmentioning
confidence: 99%
“…Furthermore chromatin structure, which refers to the chemical characteristics of the chromatin strand, may influence the initiation of replication by affecting the pre-RC assembly. There is evidence to show that histone acetylases and deacetylases play roles in the assembly of pre-RCs by interacting with, or disturbing the loading of, pre-RC elements such as the MCM complex (Burke et al, 2001;Iizuka et al, 2006;Pappas et al, 2004;Pasero et al, 2002). Finally, distal elements, such as locus control regions (LCRs) are known to affect initiation (Hayashida et al, 2006;Kalejta et al, 1998), with the initiation of replication at regions such as the human β-globin locus being controlled by a 5' LCR (Aladjem et al, 1995).…”
Section: Replication Initiationmentioning
confidence: 99%